Behavioral Health and Firefighters: An Intervention and Interviews with Canadian Firefighters. Issue 4 (19th May 2017) - Sommerfeld, Anne; Wagner, Shannon L.; Harder, Henry G.; Schmidt, Glen
ABSTRACT: The present study described participatory action research regarding behavioral health of firefighters. At the request of the participant fire department, the Veterans' Affairs Wellness kit was used to provide wellness information to members. During the intervention, qualitative data from the researcher perspective was collected and subsequently coded to reveal themes about lessons learned during provision of the materials. Following the intervention at the department level, individual interviews were completed with a subsample of members and their spouses. The combined outcomes from these two research phases suggest that wellness interventions for firefighters should be informal, firefighter-specific, focused on programs endorsed by firefighter-related organizations, and supported by management and frontline supervisors. From our data, we suggest that the Veterans' Affairs Wellness kit should be studied further as a potentially meaningful fire service intervention. Further, we propose that this and other interventions should take into account job aspects identified as important by both members and their spouses.